Are Functional and Activity Limitations Becoming More Prevalent among 55 to 69-Year-Olds in the United States? - Choi, HwaJung (PLoS One, 2016)
OBJECTIVES: This study examines changes in functional and activity limitations 1998–2012 for individuals 55–69. METHODS: Logistic models are used to estimate trends in limitations in vision, hearing, physical and cognitive functioning, IADLs, and ADLs. Additional models assess the extent to which trends are associated with and differ by education, smoking, and BMI. RESULTS: Changes in prevalence of limitations in vision, hearing, cognitive functioning, and ADLs are not statistically significant. Limitations in physical functioning declined by 0.37% per year. IADL limitations increased by 1.33% per year, but most of the increase occurred between 2008 and 2010/2012, and are associated with economic hardship during the Great Recession. Increases in education are especially beneficially associated with trends in limitations, but reductions in smoking also appear to be advantageous for some outcomes. Increases in BMI are associated with trends in physical functioning, IADL, and ADL limitation. DISCUSSION: For Americans 55–69, functional and activity limitations were largely unchanged 1998–2012. Our results suggest that if educational attainment had not increased, most functional and activity limitations potentially could have worsened substantially. Future change in educational attainment is not expected to be so positive. Continued monitoring of trends in activity limitations might well include greater focus on the explanatory roles of environmental factors, including economic circumstances.